She Could Not Agree More: The Role of Failure Attribution in Shaping the Gender Gap in Competition Persistence - Manar Alnamlah; Christina Gravert (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
In competitive and high-reward domains such as corporate leadership and entrepreneurship, women are not only underrepresented but they are also more likely to drop-out after failure. In this study, we conducted a laboratory experiment to investigate the influence of attributing failure to one of the three causal attributions - luck, effort, and ability - on the gender difference in competition persistence. Participants compete in a real effort task and then their success or failure is attributed to one of three causal attributions. We find significant gender differences in competition persistence when failure is attributed to a lack of ability, with women dropping out more. On the contrary, when suggested that failure was due to lack of luck, women's competition persistence after failure increases relative to men. We find no gender difference when failure is attributed to a lack of effort. Our findings have important implications for designing feedback mechanisms to reduce the gender gap in competitive domains.
Keywords: C91; D03; M50; J24; 330; decision analysis; competition; gender gap; performance feedback; laboratory experiment